Global Politics of Knowledge Production: The Challenges of Islamization of Knowledge in The Light of Tradition Vs Secular Modernity Debate - Abdin Chande (Nazhruna: Jurnal Pendidikan Islam, 2023)
This paper argues that the main objective of the ‘Islamization of knowledge’ project is to assert Muslim ownership over their institutions by developing an alternative system of learning/knowledge production that serves as a foundation for re-inventing/renewing the Islamic traditions to cope with the multitude of challenges that Muslims face today. These challenges stem from a number of intertwining factors that influence this process, including the modern advances that accompanied the colonial and post-colonial developments that shaped and reshaped the intellectual culture and institutions of Muslim and non-Muslim societies precisely by allowing Western methodological approaches to set the agenda and the objectives of the schools. Accordingly, proponents of the Islamization of knowledge such as Naquib al-Atas, Ismail al-Faruqi, Taha Jaber al-Alwani, and others have developed their own different approaches to the production of knowledge and in so doing have generated a philosophical discourse that offers a critique of modern/Western knowledge and its epistemological and methodological assumptions. What, therefore, has been the outcome of the Islamization of knowledge project in terms of producing, for instance, Islamic social sciences, broadly defined, in the areas of, say, economics, sociology, political science, and so on? How have normative teachings of Islam, its ethical concerns, and Muslim efforts to come to terms with modernity (an ideology that carries the values and ideas of triumphant capitalism and secularism) been incorporated into these disciplines to counter or respond to Western hegemony and Eurocentric and orientalist order of knowledge? Finally, have Muslims succeeded in bringing together scholars of the text (fuqaha) and scholars of the context (experts in different fields of knowledge from social sciences to sciences) to deal with pressing modern problems that require new interpretations? This paper will attempt to answer some of these questions.